2012
DOI: 10.1175/jamc-d-11-056.1
|View full text |Cite
|
Sign up to set email alerts
|

A Climatology of Disdrometer Measurements of Rainfall in Finland over Five Years with Implications for Global Radar Observations

Abstract: To improve the understanding of high-latitude rain microphysics and its implications for the remote sensing of rainfall by ground-based and spaceborne radars, raindrop size measurements have been analyzed that were collected over five years with a Joss-Waldvogel disdrometer located in Jä rvenpä ä , Finland. The analysis shows that the regional climate is characterized by light rain and small drop size with narrow size distributions and that the mutual relations of drop size distribution parameters differ from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 41 publications
2
52
1
Order By: Relevance
“…These features are similar to the distribution of D m observed in a high-latitude region at Järvenpää, Finland (Fig. 4 of Leinonen et al, 2012). For D m values > 1.7 mm, the PDF for convective rainfall is higher than stratiform rainfall.…”
Section: Classification Of Rainfall Types and Rainfall Eventssupporting
confidence: 84%
See 1 more Smart Citation
“…These features are similar to the distribution of D m observed in a high-latitude region at Järvenpää, Finland (Fig. 4 of Leinonen et al, 2012). For D m values > 1.7 mm, the PDF for convective rainfall is higher than stratiform rainfall.…”
Section: Classification Of Rainfall Types and Rainfall Eventssupporting
confidence: 84%
“…The shape of the DSD is calculated as the ratio of D m to the standard deviation (SD) of D m (σ m in mm) (Ulbrich and Atlas, 1998;Bringi et al, 2003;Leinonen et al, 2012): …”
Section: Normalized Gamma Dsdmentioning
confidence: 99%
“…2. Assuming spheroids (Matrosov, 2007) and taking the typical vertical aspect ratio c/a = 0.6 (Korolev and Isaac, 2003;Matrosov et al, 2005b), we found that D PIP is roughly equal to 0.92 of a volume equivalent diameter. As can be seen, the conversion factor varies between 0.8 and 1.…”
Section: Particle Size Distributionmentioning
confidence: 90%
“…This approach has been implemented by numerous authors (Jaffrain and Berne, 2012a;Leinonen et al, 2012;Ryzhkov et al , 2005;Verrier et al, 2013;Gires et al, 2015). It should be mentioned that it relies on strong unrealistic hypothesis, notably the homogeneity of the DSD within a radar bin (see Gires et al, 2017b for a discussion of the limitations of this approach).…”
mentioning
confidence: 99%